2020
DOI: 10.1302/1863-2548.14.190176
|View full text |Cite
|
Sign up to set email alerts
|

Does the size of the femoral head correlate with the incidence of avascular necrosis of the proximal femoral epiphysis in children with developmental dysplasia of the hip treated by closed reduction?

Abstract: Purpose The purpose of this study was to identify if any correlation between size of the proximal femoral epiphysis and avascular necrosis (AVN) exists. Methods We retrospectively reviewed 111 patients with developmental dysplasia of the hip treated by closed reduction (124 hips). The diameter and height of both femoral head and ossific nucleus were assessed on preoperative MRI. Results The diameter and the height of the femoral head as well as of the ossific nucleus of the contralateral side were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Persistent lateral hip subluxation and dislocation result in a shallow acetabulum and a mismatched femoral head. A smaller femoral head and delayed appearance of the ossific nucleus in radiographic DDH were also found in the study of Wu et al (22) and Sugawara et al (23). More importantly, a smaller femoral head was significantly associated with the incidence of avascular necrosis (22).…”
Section: Discussionsupporting
confidence: 54%
“…Persistent lateral hip subluxation and dislocation result in a shallow acetabulum and a mismatched femoral head. A smaller femoral head and delayed appearance of the ossific nucleus in radiographic DDH were also found in the study of Wu et al (22) and Sugawara et al (23). More importantly, a smaller femoral head was significantly associated with the incidence of avascular necrosis (22).…”
Section: Discussionsupporting
confidence: 54%
“…Wu et al . [21] measured the ossific nucleus size on MRI of the patients they applied closed reduction and reported that ossific nucleus size was not related to AVN of the femoral head. Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have also showed that the incidence of poor perfusion of the femoral head on the dislocated side was significantly higher than that at contralateral side. 22 In all, 61.5% of vascular perfusion of the femoral head was partially or globally decreased on the dislocated side in patients with DDH after CR, but not decreased at the contralateral side. Tiderius et al 15 reported that pMRI was used to evaluate the perfusion changes of the femoral head after CR in 27 children (28 hips) with DDH, and the results showed that 20 hips (71.4%) showed focal, asymmetric and global decreased of perfusion of the femoral head after CR on the dislocated side.…”
Section: Discussionmentioning
confidence: 71%
“…Our previous study has also shown that the development of the femoral head on the dislocated side in patients with DDH is significantly poorer than that at the contralateral side. 22 This may be related to the lack of mutual stress stimulation between the dislocated femoral head and acetabulum, the poor development of the femoral head and the poor development of the vascular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation